Validation and measurement invariance of the Muscularity‐Oriented Eating Test among Brazilian men and women. Issue 4 (12th March 2022) - de Carvalho, Pedro Henrique Berbert; Bagolin, Vitoria; Junqueira, Alessandra Costa Pereira; Nagata, Jason M.; Cattle, Chloe J.; Murray, Stuart B.; Compte, Emilio J.; Costa, Telma Maria Braga; Almeida, Sebastião Sousa; Laus, Maria Fernanda
Abstract: Objective: The Muscularity‐Oriented Eating Test (MOET) is a 15‐item unidimensional scale, designed to assess eating practices that occur in the pursuit of a muscular body. The aim of the present study was to describe the translation and cultural adaptation of the MOET to Brazilian Portuguese, to explore its factor structure and measurement invariance, and to evaluate its internal consistency, three‐week test–retest reliability, and convergent validity in a community sample of Brazilian men and women. Method: After the back‐translation procedure, the Brazilian MOET was administered online to a sample of 1246 adults (634 men and 612 women), along with measures of drive for muscularity, muscle dysmorphia symptoms, muscular/athletic‐ideal internalization, disordered eating behaviors, and exercise dependence. Results: Findings from an exploratory factor analysis and a confirmatory factor analysis revealed a one‐factor structure and adequate internal consistency for men ( ω  = 0.86; α  = 0.86) and women ( ω  = .84; α  = .83). Measurement invariance across gender was supported. In addition, the scale demonstrated good three week test–retest reliability for both men (ICC = .96; p  < .001) and women (ICC = .92; p  < .001), and the subscales revealed moderate to large associations with drive for muscularity, muscle dysmorphia symptoms, muscular/athletic‐ideal internalization, disordered eating, and exercise dependence. Conclusion: This study supports the validity and reliability of the MOET in a community sample of Brazilian men and women and represents an advance in measures of muscularity‐oriented disordered eating in Brazilian adults, allowing for future cross‐cultural studies in this field. Public Significance: The Muscularity‐Oriented Eating Test (MOET) is a measure of muscularity‐oriented disordered eating, which assess strict adherence to diet rules, including the food's macronutrient content, regulation of protein intake, and eating less or more to influence muscle gain. This study evaluated the validity and reliability of the MOET in a community sample of Brazilian men and women. Our findings represent an advance in measures of muscularity‐oriented disordered eating in Brazilian adults.